2013
DOI: 10.1523/jneurosci.1864-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Position Information Accumulates Steadily over Time

Abstract: One of the more enduring mysteries of neuroscience is how the visual system constructs robust maps of the world that remain stable in the face of frequent eye movements. Here we show that encoding the position of objects in external space is a relatively slow process, building up over hundreds of milliseconds. We display targets to which human subjects saccade after a variable preview duration. As they saccade, the target is displaced leftwards or rightwards, and subjects report the displacement direction. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 43 publications
(5 reference statements)
5
64
2
Order By: Relevance
“…The effect of task condition on saccade latency, amplitude, and velocity measures may imply that participants in this experiment prioritized speed over accuracy in their performance of the saccade task. Spending more time preparing a saccade leads to better performance on displacement detection tasks (Zimmermann, Morrone, & Burr, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of task condition on saccade latency, amplitude, and velocity measures may imply that participants in this experiment prioritized speed over accuracy in their performance of the saccade task. Spending more time preparing a saccade leads to better performance on displacement detection tasks (Zimmermann, Morrone, & Burr, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several other recent studies are consistent with the conclusion that VWM supports the perception of stability across saccades. For example, visual factors that affect the quality of the representation of the saccade target in memory, such as contrast (Matsumiya, Sato, & Shioiri, 2016), preview duration (Zimmermann, Morrone, & Burr, 2013), and size (Zimmermann, 2016) have been shown to affect displacement perception across saccades.…”
Section: Chapter 8: General Discussionmentioning
confidence: 99%
“…More recently, Rand and Shimansky (2013) have modeled reaching movements in terms of progressively refined control. The progressive refinement of motor control could be due in part to the accumulation of spatial position information over time as suggested by Zimmermann et al (2013). Given the time requirements of the present task (i.e., completion within 2 sec), the subject may have initiated movement before fully localizing the target and programming the movement.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been termed saccadic suppression of displacement. We have recently shown that performance in this paradigm drastically improves if the visual system has time to build up a stable representation of the saccade target location (Zimmermann et al, 2013). The longer participants had seen the saccade target before executing the saccade, the better they were able to discriminate the displacement direction.…”
Section: Introductionmentioning
confidence: 99%